New Detections of Feldspar‐Bearing Volcanic Rocks in the Walls of Valles Marineris, Mars. Issue 2 (24th January 2023) - Flahaut, Jessica; Payet, Vincent; Fueten, Frank; Guitreau, Martin; Barthez, Marie; Ito, Gen; Allemand, Pascal
Abstract: Plagioclase‐bearing rocks were first detected in the vicinity of large impact basins on Mars using visible/near‐infrared (VNIR) data. The geologic context is consistent with excavated plutons or ancient crustal outcrops. Our analyses reveal plagioclase outcrops exposed in a 200 m thick, sub‐horizontal layer in the 8 km deep walls of the Valles Marineris canyon. These plagioclase‐bearing rocks are consistent with either a sill, a volcano‐clastic layer, or a porphyritic lava flow, in contrast with the previous understanding that plagioclase feldspar signatures must be indicative of nearly pure, anorthositic rocks inherited from a primary flotation crust or granitoids from either plutonic activity or ancient continental crust. We present here evidence of possibly effusive, volcanic rocks bearing plagioclase VNIR spectral signatures, expanding the geologic setting of these unique and uncommon martian rocks to include multiple lithologies. This has direct implications for Mars magmatic processes and for the nature of its crust. Plain Language Summary: Detection of plagioclase feldspar minerals from remote sensing instruments onboard Mars missions is difficult, and only a handful of occurrences have been reported so far. We present here new detections of such minerals in the giant Martian canyon of Valles Marineris (VM), exposed in their original context, and associated at least in one location, to a 200 m thick sub‐horizontal layer within the walls. Analyses were performed using visible near‐infrared spectral data, which are commonly compared to reference spectra of known terrestrial minerals, or mineral powders, acquired in the laboratory. Whereas previous detections were interpreted as evidence for plagioclase‐dominated, or at least, nearly mafic‐free, plutonic rocks, we argue here that the VM outcrops correspond to erupted, volcanic products. The signature of plagioclase could originate from large crystals hosted in mafic, intermediate, or felsic volcanic rocks; from a lava flow, or from welded ashes. Our new observations confirm that plagioclase detections on Mars can correspond to multiple types of rocks and bring more clues to ongoing debates regarding the extent of Mars magmatic processes and the nature of its crust. Key Points: Eight new detections of plagioclase‐like signatures are reported in their original geologic context in the walls of Valles Marineris At one location, the possible feldspar signatures are clearly associated with a 200 m thick sub‐horizontal layer, hinting at an eruptive origin Plagioclase detections on Mars are uncommon but include multiple lithologies, with various implications for magmatic processes